Penyelesaian Konflik Lahan Desa Chilonga - Newman Sango; Ichsan Malik; I Gede Sumertha KY (International Journal Of Humanities Education and Social Sciences (IJHESS), 2023)
The Ministry of Lands, Agriculture, Water, Climate, and Rural Resettlement issued statutory instrument (S.I) 50 of 2021, announcing the 12940 hectares of Chilonga land is commercialized for national food security. The statutory instrument (S.I) 50 of 2021 also stated that the Chilonga villagers immediately pave way for the lucerne grass irrigation project. The problem with this research is that the Ministry of Land has the power to relocate people in all communal lands according to the constitution of Zimbabwe and the Communal lands Act Chapter 20:04, but failed to resettle the Chilonga villagers. This research aims to analyze the causes of the Chilonga land conflict, the Ministry of Lands's capacity to carry out the Chilonga land resettlement, and how the government can intervene in resolving the Chilonga land conflict. Theories and concepts used are; strategy theory, conflict tree concept, conflict triangle theory, and national security concept. This research employs a qualitative research method involving nine informants. The results of the study show that the causes of the Chilonga land conflict are poor strategic planning, poor communication, cultural beliefs, political influence, lack of trust, and land compensation. The research results also show that the Ministry is lacking the capacity to conduct Chilonga resettlement. Finally, the research shows that the government should provide adequate support to the resettlement program and also should consider win-win conflict resolution.